Makna Asosiasi dalam Novel Negeri 5 Menara Karya A. Fuadi Sebagai Alternatif Bahan Ajar Mata Kuliah Semantik - Hanifah, Ifah; Fitriati, Siti (JURNAL PESONA, 2017)
Abstract TThis study aims to analyze the meaning of associations in the novel Negeri 5 Menara as alternative teaching materials semantic courses on students PBSI FKIP UNIKU. This research method is descriptive qualitative, that describes the meaning of association in Novel Negeri 5 Menara and its conformity with the principle of preparation of teaching materials. After examined and analyzed and conducted the discussion obtained the following conclusions. 1) Text in Novel Negeri 5 Menara of A. Fuadis work has the meaning of association consisting of the meaning of reflection, affection, connotation, collocation, and stylistic. Among these meanings, the most dominant is the meaning of affection and reflection, and 2) The text in the Novel Negeri 5 Menara can be an alternative teaching material in the Semantic Subject course on the meaning of the association because it meets the requirements of relevance, consistency, adequacy, conformity with the language development of learners, and in accordance with the characters values. Keywords: Association meanings, Instructional Materials, Semantics